Psicodiagnóstico interventivo em idosos depressivos - Falbo, José Guilherme Almeida Campos (2015)
This work had as primary objective to verify the use of the interventive psychodiagnosis as a clinic psychoadignosis procedure in elderly patients with the depression diagnosis. To that end, it has been used the Paulo´s (2004) model in a four elderly women group whit ages higher than 60 years old, and that fit in the depression diagnosis. As a method proposal for the degree of depression evaluation it has been used the Beck´s Depression Inventory, being the score of each participant the inclusion criterion for the study. The Phillipson object relation test was also used, as well as a questionnaire dissertation as an instrument for psychodiagnosis. At the end of this study it was possible to observe a drop in the Beck inventory score in three of the four participants in relation to the beginning of the study